Investigation of smart grid technologies deployment for energy reliability enhancement in electricity distribution networks - Lukas M.N. Gabriel; John A. Adebisi; Leokadia N.P. Ndjuluwa; Dickson K. Chembe (Franklin Open, 2025)
This study investigates the deployment of smart grid technologies in electricity distribution networks for possible improvement of energy reliability and continuity of energy supply to consumers. Recently energy distribution companies have been observed to have been challenged with power disruptions, which mostly experienced during the rainy season. These disruptions are as results of growing demand, aging infrastructures, lack of advanced technologies and dependability on major utility companies for power supply hence this study. This investigative research used both qualitative and quantitative methodologies to identify potential opportunities and challenges associated with smart grid technologies deployment into distribution networks using Central North Regional Electricity Distributor (CENORED) and Namibia Power Corporation (NAMPOWER) as a case study for the possibility of smart technologies deployment to enhance energy distribution network. Questionnaires and interviews were administered for engineers and stakeholder with over 80 % respondents in agreement that the deployment of Distributed Energy Resources (DERs) and Demand Side Response (DSR) can improve network reliability while 100 % respondents aligned that Fault Location, Isolation and Service Restoration technology (FLISR) can help them improve the performance of their network. CENORED network was modeled using ETAP software for performance evaluation. Result from this study shows that DERs, FLISR and DSR possess a potential to improve distribution network reliability and possible implementation.